ANALISIS PEMASARAN LADA (Piper Nigrum L) DI DESA SANGLEPONGAN KECAMATAN CURIO KABUPATEN ENREKANG - -, Nurfitri; -, Yusriadi; -, Arman (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
Marketing plays an important role in a business that is run. The indicator of a product’s marketing success is a marketing channel that takes placeeffetively and efficinly. Pipper commodities are very important role in the Indonesian economy both as a source of income society and foreign exchange earners. The main target of pipper product’s in Indonesian today is for export so that the price is strongly influenced by the price of pipper in the world market. The purpose of this research is to know the marketing channel and efficiency of pipper marketing in Sanglepongan Village, Curio Sub District, Enrekang Regency. The basic method of descriptive research and its implementation by survey technique. Data used primer data and secondary data. Data collection techques are carried out by observation, interviews, questionnaires and documentation.The results of this study indicate that are three marketing nhannels formed in the village of Sanglepongan namely :Channel I, II and III patterns where the efficiency level of pepper marketing is the most efficient in channel I pattern with a value of 0%. Channel II pattern with a value of 0,87%.